2016
DOI: 10.1080/00365521.2016.1244705
|View full text |Cite
|
Sign up to set email alerts
|

Wheat challenge in self-reported gluten sensitivity: a comparison of scoring methods

Abstract: Clinician diagnosed 85% with NCGS. The proportion of NCGS was lower according to the Salerno and Monash cut-offs. The Salerno cut-off should be the starting point for a common definition of symptom change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(40 reference statements)
2
3
0
Order By: Relevance
“…However, the method is established as a tool to monitor response during gluten challenge in celiac disease and NCGS patients. 25,43 Further, the daily scored VAS scales that have been used in similar challenge studies 12,14 confirmed the main findings of GSRS-IBS in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…However, the method is established as a tool to monitor response during gluten challenge in celiac disease and NCGS patients. 25,43 Further, the daily scored VAS scales that have been used in similar challenge studies 12,14 confirmed the main findings of GSRS-IBS in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Noteworthy, when the gluten re-challenge was performed according to the current recommended procedure (i.e., the Salerno criteria) the overall percentage of patients relapsing after gluten was significantly higher as compared to placebo (40 vs. 24%; p = 0.003), and the meta-analysis showed a highly significant RR and IRR of relapse after gluten as compared to placebo. This finding supports the existence of a causal relationship between gluten and relapsing symptoms, and strongly suggest to follow the Salerno expert recommendations when suspecting the diagnosis of NCGS, until a valid biomarker will be available, as previously reported (Skodje et al, 2017 ). This is further supported by the results of the meta-correlation analysis showing that the percentage of relapse was highly correlated with the amount of gluten and the duration of challenge.…”
Section: Discussionsupporting
confidence: 88%
“…This has not been the experience when populations with self‐reported NCGS have been studied. For instance, two surveys of patients who reported they were gluten sensitive, even those strictly on a GFD, remained moderately symptomatic . This was confirmed in the setting of a clinical trial with symptoms assessed by daily entries into a diary using a visual analogue scale .…”
Section: The Root Of the Controversymentioning
confidence: 78%